Direct plasma irradiation affects expression of RNAs in cultured mammalian cells. (1st November 2016) - Kobayashi, Mime; Tokaji, Hideto; Kumagai, Shinya
Abstract: The expression of RNAs in mouse NIH3T3 cells was altered by low-temperature atmospheric-pressure plasma irradiation. Cell culture liquid media were removed before plasma irradiation so that direct plasma effects can be assessed. After 5 s irradiation, the cells were cultured in media for 1 or 3 h and RNA expression was analyzed using a microarray. When analyzed 1 and 3 h after plasma irradiation, the upregulation of hypothetical transmembrane proteins and U3 small nucleolar RNAs was detected at both time points. Our results provide a basic principle for understanding the molecular mechanisms of plasma effects on mammalian cells.